2006
DOI: 10.1109/tit.2006.874379
|View full text |Cite
|
Sign up to set email alerts
|

Optimal throughput-delay scaling in wireless networks - part I: the fluid model

Abstract: Gupta and Kumar (2000) introduced a random model to study throughput scaling in a wireless network with static nodes, and showed that the throughput per source-destination pair is Θ 1/ √ n log n . Grossglauser and Tse (2001) showed that when nodes are mobile it is possible to have a constant throughput scaling per source-destination pair.In most applications delay is also a key metric of network performance. It is expected that high throughput is achieved at the cost of high delay and that one can be improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
452
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(465 citation statements)
references
References 22 publications
(50 reference statements)
13
452
0
Order By: Relevance
“…There has been some recent interesting work on characterizing the delay performance of scheduling algorithms, or formulating scheduling and routing policies in random networks that attain order-optimal delay [6], [7], [20], [14], [16], [17]. Most of these works do not consider queuing delay, and focus on attaining order-optimal packet delivery delay in presence of node mobility.…”
Section: Related Workmentioning
confidence: 99%
“…There has been some recent interesting work on characterizing the delay performance of scheduling algorithms, or formulating scheduling and routing policies in random networks that attain order-optimal delay [6], [7], [20], [14], [16], [17]. Most of these works do not consider queuing delay, and focus on attaining order-optimal packet delivery delay in presence of node mobility.…”
Section: Related Workmentioning
confidence: 99%
“…In [7], it was first shown that mobility improves capacity. Subsequently, communication delay has been studied under various node mobility models such as Markov [9], [10], random way point [11], and Brownian [12]. General observation has been that increasing node speed improves communication delay.…”
Section: A Related Workmentioning
confidence: 99%
“…Thus, the variable v is the maximum speed that vehicles in the network can possibly achieve. Random waypoint and Markov mobility are two examples of such motion models [9], [11], [16], [17].…”
Section: A Mobility Modelmentioning
confidence: 99%
“…In Part I of this two-part paper, capacity scaling laws for underwater networks are analyzed in an extended network [5,4,10,25,26] of unit node density, which is one of fundamentally different network models. Part II [27] shows the analysis for a dense network [1,6,10] of unit area used as another extreme network realization. 4 Unlike the work in [23], the information-theoretic notion of network capacity is adopted in terms of characterizing the model for successful transmission.…”
Section: (Ii) F (X) = O (G(x)) Means That Lim X→∞ F (X)mentioning
confidence: 99%
“…They showed that the total throughput scales as Θ √ n/ log n when a multi-hop (MH) routing strategy is used for n source-destination (S-D) pairs randomly distributed in a unit area. 1 MH schemes are then further developed and analyzed in [3][4][5][6][7][8][9], while their throughput per S-D pair scales far slower than Θ (1). Recent results [10,11] have shown that an almost linear throughput in the radio network, i.e.…”
Section: Introductionmentioning
confidence: 99%